Measurement of the presence of $a_1(1420)$ and $ω(782)$ in $τ^{-}→ π^{-}π^{+}π^{-}ν_{τ}$ at Belle - Rabusov, Andrei; Greenwald, Daniel; Paul, Stephan (SciPost physics proceedings, 2025)
We present preliminary results of a partial-wave analysis of \tau^-\to\pi^-\pi^-\pi^+\nu_\tau τ − → π − π − π + ν τ using data from the Belle experiment at the KEKB \mathrm{e}^+\mathrm{e}^- e + e − collider. We validate our model with a model-independent analysis. We see the \mathrm{a}_1(1420) a 1 ( 1420 ) and a G-parity-violating 1^-[\omega(782)\pi]_\mathrm{P} 1 − [ ω ( 782 ) π ] P wave in tauon decays. Our results will improve models used in simulation studies necessary for measuring the electric and magnetic dipole moments and Michel parameters of the \tau τ .